2019
DOI: 10.3390/app9214510
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy Analysis of Free Fatty Acid in Olive Oil

Abstract: Featured Application: Reliable and rapid analysis of free fatty acid (FFA) in olive oil is possible from the relative intensity ratio of characteristic vibrational modes observed by Raman spectroscopy.Abstract: Free fatty acid (FFA) is one of the most critical parameters for evaluating the quality of olive oil. In this paper, we present a simple and rapid Raman spectroscopy method for analyzing free fatty acid in olive oil. First, FFA degradation of carotenoids in olive oil is confirmed by analyzing the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Similar to the PL, the addition of adulterant oils leads to a decrease in the I 1523 /I 1656 integral ratio. Qui et al recently observed a similar result using the I 1523 /I 1656 ratio to determine the free-fatty-acid (FFA) content of olive oils and found that this intensity ratio decreases linearly with FFA content, although the FFA content was obtained from the nutrition label of each of the oils [21]. Thus, the I 1523 /I 1656 integral ratio is an additional useful figure of merit to quantify EVOO purity.…”
Section: Assignment Of the Common Raman Bands Among The Edibles Oilsmentioning
confidence: 78%
See 1 more Smart Citation
“…Similar to the PL, the addition of adulterant oils leads to a decrease in the I 1523 /I 1656 integral ratio. Qui et al recently observed a similar result using the I 1523 /I 1656 ratio to determine the free-fatty-acid (FFA) content of olive oils and found that this intensity ratio decreases linearly with FFA content, although the FFA content was obtained from the nutrition label of each of the oils [21]. Thus, the I 1523 /I 1656 integral ratio is an additional useful figure of merit to quantify EVOO purity.…”
Section: Assignment Of the Common Raman Bands Among The Edibles Oilsmentioning
confidence: 78%
“…Apart from these official methods, there are a number of alternative and complementary methods that have been suggested over the past decade. Among them, infrared and Raman spectroscopy are gaining attention [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The EVOO samples from the three different varieties were also analyzed using Raman spectroscopy. Figure 7 depicts a characteristic Raman spectrum of olive oil in the range 1000-1700 cm −1 after the background subtraction, using the Zhangfit technique [31] Table 4 shows the characteristic Raman bands and their corresponding assignments to vibrational modes of the functional groups [13,14,32]. Those bands correspond to the fatty acids contained in the sample, with the peaks located at 1265 and 1657 cm −1 corresponding to the unsaturated fatty acids.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…In addition to proper sample preparation, selection of appropriate analytical tool is paramount for fatty acid analysis. Wide range of analytical tools, including GC [ 173 , 174 , 176 , 179 , 182 ], GC-MS, gas-chromatography vacuum ultraviolet spectroscopy (GC-Vacuum UV) [ 178 ], gas-chromatography coupled with flame ionization detection (GC-FID) [ 170 , 172 ], liquid Chromatography-High Resolution Mass Spectrometry (LC-HRMS) [ 171 , 183 ], UHPLC-MS/MS [ 142 ], Raman spectroscopy [ 181 ], FTIR [ 188 , 189 ] and many more improved platforms have been used to perform FA analysis. Fatty acid analysis in LC-MS instrument showed some drawbacks in term of larger solvent consumption and lower selectivity [ 190 ].…”
Section: Fatty Acids and Cholesterolmentioning
confidence: 99%
“…Raman spectra have significant advantage with aqueous systems as it is unobtrusive and able to detect grouped FA, such as total SFA, MUFA, PUFA, conjugated linoleic acid (CLA) and others. Qiu et al [ 181 ] quantitated FAs in olive oil without any pre-treatment of the sample using Raman spectroscopy. While Liu et al [ 165 ] combined GC-MS and LC-MS to analyze fatty acids in milk.…”
Section: Fatty Acids and Cholesterolmentioning
confidence: 99%